2015
DOI: 10.1073/pnas.1417143112
|View full text |Cite
|
Sign up to set email alerts
|

Ocean fronts drive marine fishery production and biogeochemical cycling

Abstract: Long-term changes in nutrient supply and primary production reportedly foreshadow substantial declines in global marine fishery production. These declines combined with current overfishing, habitat degradation, and pollution paint a grim picture for the future of marine fisheries and ecosystems. However, current models forecasting such declines do not account for the effects of ocean fronts as biogeochemical hotspots. Here we apply a fundamental technique from fluid dynamics to an ecosystem model to show how f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
135
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 37 publications
6
135
0
Order By: Relevance
“…The shortfin mako shark Isurus oxyrinchus (hereafter: mako), is an upper level pelagic predator that is globally distributed throughout temperate and tropical oceanic regions. Although highly‐mobile and capable of engaging in long distance movements, tracking studies demonstrate that mako populations exhibit high fidelity to particular oceanic regions (Block et al 2011, Rogers et al , Vaudo et al 2017, Francis et al 2019). This trait can be exploited to develop natural experiments, in which mako sharks across oceanic regions are studied in a methodologically consistent manner, facilitating meaningful comparisons between ecosystems (McIntire and Fajardo ).…”
Section: Introductionmentioning
confidence: 99%
“…The shortfin mako shark Isurus oxyrinchus (hereafter: mako), is an upper level pelagic predator that is globally distributed throughout temperate and tropical oceanic regions. Although highly‐mobile and capable of engaging in long distance movements, tracking studies demonstrate that mako populations exhibit high fidelity to particular oceanic regions (Block et al 2011, Rogers et al , Vaudo et al 2017, Francis et al 2019). This trait can be exploited to develop natural experiments, in which mako sharks across oceanic regions are studied in a methodologically consistent manner, facilitating meaningful comparisons between ecosystems (McIntire and Fajardo ).…”
Section: Introductionmentioning
confidence: 99%
“…These challenges have led many to forgo explicit trophodynamic approaches to understand catch constraints in favor of exploring correlations with diverse oceanographic indicators, such as average chlorophyll and variability, the presence or strength of fronts, ecosystem size, and dispersal properties (14)(15)(16)(17)(18). Others have included subsets of trophodynamic factors within large multifactor regressions (19,20).…”
mentioning
confidence: 99%
“…Oceanic fronts, strong horizontal gradients in temperature, salinity and/or density, are biogeochemical hotspots caused by the physics associated with the abutment of water masses with different properties (Lévy et al ; Woodson and Litvin ). The increased remote and in situ sampling of our oceans in recent decades has demonstrated that fronts are ubiquitous features, occurring across a spectrum of temporal and spatial scales (Lévy et al ).…”
mentioning
confidence: 99%